2021
DOI: 10.5056/jnm20134
|View full text |Cite
|
Sign up to set email alerts
|

Inter-hemispheric Functional Connections Are More Vulnerable to Attack Than Structural Connection in Patients With Irritable Bowel Syndrome

Abstract: Background/AimsIrritable bowel syndrome (IBS) is a prevalent functional gastrointestinal disease characterized by recurrent abdominal pain and bowel dysfunction. However, the majority of previous neuroimaging studies focus on brain structure and connections but seldom on the inter-hemispheric connectivity or structural asymmetry. This study uses multi-modal imaging to investigate the abnormal changes across the 2 cerebral hemispheres in patients with IBS. MethodsStructural MRI, resting-state functional MRI, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…The cortical thickness of primary somatosensory cortex was associated with pain intensity in female irritable bowel syndrome (IBS) patients ( Grinsvall et al, 2021 ). Previous studies have reported aberrant activity and function of sensorimotor network in functional GI disorders ( Mayer et al, 2009 ; Duan et al, 2021 ; Liu G. et al, 2021 ). Moreover, we observed that altered PAS scores in the right postcentral gyrus had inverse correlation to sleep disturbance in MDD, implying that FC of postcentral gyrus corresponded with sleep quality, which was consistent with previous studies ( Huang et al, 2012 ; Klumpp et al, 2018 ).…”
Section: Discussionmentioning
confidence: 95%
“…The cortical thickness of primary somatosensory cortex was associated with pain intensity in female irritable bowel syndrome (IBS) patients ( Grinsvall et al, 2021 ). Previous studies have reported aberrant activity and function of sensorimotor network in functional GI disorders ( Mayer et al, 2009 ; Duan et al, 2021 ; Liu G. et al, 2021 ). Moreover, we observed that altered PAS scores in the right postcentral gyrus had inverse correlation to sleep disturbance in MDD, implying that FC of postcentral gyrus corresponded with sleep quality, which was consistent with previous studies ( Huang et al, 2012 ; Klumpp et al, 2018 ).…”
Section: Discussionmentioning
confidence: 95%
“…This systematic review comprised 22 rs-fMRI studies aimed at characterizing brain function (Li et al, 2013(Li et al, , 2018Zeng et al, 2013;Ma et al, 2014Ma et al, , 2015Gui et al, 2015;Ke et al, 2015;Qi et al, 2015Qi et al, , 2016aWeng et al, 2016;Qin et al, 2017;Wang et al, 2017;Nan et al, 2019aNan et al, ,b, 2021Ao et al, 2021;Chen et al, 2021;Geng et al, 2021;Liu et al, 2021). These studies were conducted at a variety of research sites around China and contained a sample size of at least 10 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The diagnostic criteria for IBS in the included studies were respectively ROME III (Longstreth et al, 2006) in 19 studies (Li et al, 2013(Li et al, , 2018Zeng et al, 2013;Ma et al, 2014Ma et al, , 2015Gui et al, 2015;Ke et al, 2015;Qi et al, 2015Qi et al, , 2016aWeng et al, 2016;Qin et al, 2017;Wang et al, 2017;Nan et al, 2019a,b;Ao et al, 2021;Chen et al, 2021), ROME IV (Drossman, 2016) in one study (Geng et al, 2021), and undefined criteria in one study (Nan et al, 2021). For IBS categories, five studies included IBS-Diarrhea (IBS-D) patients (Ke et al, 2015;Wang et al, 2017;Ao et al, 2021;Chen et al, 2021;Geng et al, 2021), and one study (Liu et al, 2021) included patients with different IBS categories, including IBS-constipation (IBS-C), IBS-mix (IBS-M) and IBS-D. Two studies by Li J's team explored IBS with or without depression versus HCs (Li et al, 2018. Table 1 summarized the study's characteristics.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations